Analisis Peningkatan keandalan Oil Switch Breaker pada Capacitor Bank 13,8kV Melalui Program Major Overhaul - Doloksaribu, Rio; kusuma, Galih; Sudarwanto, Yuni; Haifan, Mohamad (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
Oil Switch Breaker (OSB) serves as the primary protection component in capacitor banks within the 13,8 kV distribution network of PT Pertamina Hulu Rokan, safeguarding the system against overvoltage disturbances. Pole-mounted outdoor OSBs demonstrate low reliability due to environmental exposure, insulating oil degradation, and inadequate maintenance programs. This study analyzes OSB reliability enhancement through a major overhaul program based on field case studies. Methods employed include insulating oil breakdown voltage (BDV) testing per ASTM D1816, root cause analysis for failure investigation, and pre/post-overhaul performance evaluation. Results reveal pre-maintenance BDV values of 25-28 kV caused capacitor bank failures and 8 hours 45 minutes downtime with power factor at 0.82; post-overhaul with spare units, BDV improved to ≥35 kV, power factor rose to 0.96, and no disturbances occurred during subsequent monitoring. The major overhaul program effectively enhances OSB reliability and system availability.